1992
DOI: 10.1002/eji.1830221131
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin (IL)‐1β, IL‐6 and their respective receptors in the normal rat brain and after injury

Abstract: The expression of interleukin (IL)-1 beta, IL-6 and their respective receptors has been studied in the rat brain before and up to 24 h after injury. Messenger RNA transcripts of these four genes were detected by in situ hybridization (ISH) in different structures of the intact brain. The distribution was very similar for IL-1 beta, IL-6 and IL-6 receptor (IL-6R). The expression of IL-1R was more widespread. Within hours after injury, an increased expression of IL-1 beta, and thereafter of IL-6 was documented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
2
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(82 citation statements)
references
References 27 publications
6
70
2
4
Order By: Relevance
“…However, IL-6 immunoreactivity revealed a weak constitutive produc tion in these areas of control brain, thus confirming ear-lier results at the mRNA level. The discre p ancy between our in situ hybridization findings and those reported by others may result from methodology, in this case immu nodetection of DIG-labeled p robes versus radioactively labeled ones (Yan et al, 1992;Schobitz et al, 1993), or p olymerase chain reaction from tissue extracts (Gadient and Otten, 1994a,b). Therefore, we regard cells exhibit ing positive staining as foci of an extremely upregulated transcription/decreased degradation of IL-6 mRNA.…”
Section: Discussionmentioning
confidence: 48%
“…However, IL-6 immunoreactivity revealed a weak constitutive produc tion in these areas of control brain, thus confirming ear-lier results at the mRNA level. The discre p ancy between our in situ hybridization findings and those reported by others may result from methodology, in this case immu nodetection of DIG-labeled p robes versus radioactively labeled ones (Yan et al, 1992;Schobitz et al, 1993), or p olymerase chain reaction from tissue extracts (Gadient and Otten, 1994a,b). Therefore, we regard cells exhibit ing positive staining as foci of an extremely upregulated transcription/decreased degradation of IL-6 mRNA.…”
Section: Discussionmentioning
confidence: 48%
“…An elevation of IL-6 level in the brainstem, including the spinal trigeminal complex, is found after trigeminal nerve injury in the rat (Anderson and Rao, 2001). Different from the response to direct brain injury (Yan et al, 1992), the induction of central cytokines after peripheral injury involves more complicated and still unknown pathways at both spinal and trigeminal levels. Our results suggest that the proinflammatory cytokine IL-1␤ was selectively induced in astroglia in the Vi/Vc transition zone after inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…More recent studies have revealed that this cytokine also arises from both the parenchyma and the fiber tracts (corpus callosum, anterior commissure, fimbria, lateral olfactory tract, optic tract, internal capsule, and corticospinal tracts within the caudate) of the CNS (Schobitz et al, 1993) and can be localized in several neuronal types including pyramidal and granular neurons of the hippocampus, neurons of the habenular nucleus, ventromedial and medial preoptic nuclei of the hypothalamus, cerebellar granular neurons, and pyramidal neurons of the cerebral cortex (Schobitz et al, 1993). Its presence in white matter suggests the expression of IL-6 by oligodendrocytes, the CNS cell type responsible for myelination of axons that comprise the fiber tracts (Yan et al, 1992).…”
Section: Il-6: a Prototype Proinflammatory Cytokine Of The Cnsmentioning
confidence: 99%